Citizenship on probation: Understanding the labour market exclusion of criminalized people in Scotland. (September 2022) - Weaver, Beth; Jardine, Cara
The significance of employment to desistance and social integration is well established, yet 62% of those subject to a Community Payback Order in Scotland are unemployed (Scottish Government, 2022). This paper reports on the findings from a small-scale survey conducted with 29 people subject to community supervision in Scotland, to shed light on the various enablers and barriers they encounter in seeking, starting and sustaining employment, and their experiences of engaging in or with employment support initiatives.